Lack of association of two chromosome 10q24 SNPs with Alzheimer’s disease - Minster, Ryan L. (2006)
Several groups have reported evidence of linkage on chromosome 10 to late-onset Alzheimer’s disease (LOAD). In a recent scan of single nucleotide polymorphisms (SNPs) on chromosome 10, significant associations between the rs498055 and rs4417206 SNPs and risk of LOAD were observed. We examined the association of these two SNPs with LOAD risk in a large Caucasian American cohort comprising about 2,000 cases and controls. Neither SNP revealed significant association with LOAD risk or age-at-onset.